(untitled) (TAMADDUN NURI JURNALI, 2024)
This study investigates the indispensable role of kinetic units, including gestures and body movements, in multimodal communication. It highlights their contribution to enhancing verbal interactions, conveying cultural meanings, and expressing emotional states. The interdisciplinary approach integrates linguistic, psychological, and cultural perspectives, providing insights into their structural, functional, and cultural dimensions.